Pelatihan Pembuatan Abon Pepaya Muda Kepada Kelompok Wanita Tani di Dusun Pidendang Desa Pemepek Kecamatan Pringgarata Kabupaten Lombok Tengah - Ni Luh Putu Sherly Yuniartini; Afe Dwiani; Suburi Rahman; Rizki Nugrahani (Rengganis Jurnal Pengabdian Masyarakat, 2022)
Papaya is a fruit that is known to many people, especially in Indonesia. Papaya also contains high nutrients, like vitamins and minerals. So far, papaya fruit has only been used for direct consumption, especially ripe fruit. Pidendang has high agricultural potential, as every yard has papaya plants. Raw papaya fruit has only been used as a vegetable. Therefore, it is necessary to make innovative processes for raw papaya fruits. One of the processing is the manufacture of papaya floss. This service aims to process young papaya into shredded so that it can be developed by women's groups in Pidendang, Pemepek Village, Pringgarata District, Central Lombok. The method of carrying out activities is a discussion with the giving of materials, training on making papaya floss, and packaging processes. The training on making papaya floss with the frying process was successfully carried out and resulting in a crispy texture and good taste.